Structural Characterization, Technofunctional and Rheological Properties of Sesame Proteins Treated by High-Intensity Ultrasound - Gul, Osman; Saricaoglu, Furkan Turker; Atalar, Ilyas; Gul, Latife Betul; Tornuk, Fatih; Simsek, Senay (MDPI AG, 2023)
Plant-derived proteins, such as those from sesame seeds, have the potential to be used as versatile food ingredients. End-use functionality can be further improved by high-intensity ultrasound treatments. The effects of high-intensity ultrasound on the properties of sesame protein isolates from cold-pressed sesame cake were evaluated. The SDS-PAGE demonstrated no significant changes in the molecular weight of proteins. Ultrasound treatments resulted in decreased particle size with a more uniform distribution, resulting in the exposure of hydrophobicity and free −SH groups and increased zeta potential. Although FTIR spectra of proteins were similar after ultrasonication, a partial increase in the intensity of the amide A band was observed. The ultrasound significantly (p < 0.05) affected the secondary structure of proteins. While optical micrographics revealed a dispersed structure with smaller particles after treatments, microstructural observations indicated more rough and irregular surfaces. Water solubility was improved to 80.73% in the sample subjected to 6 min of ultrasonication. Sesame protein solutions treated for 4 and 6 min exhibited viscoelastic structure (storage modulus (G′) > loss modulus (G′′)). In addition, the gelation temperature of proteins decreased to about 60–65 °C with increasing treatment time. Overall, ultrasound is a useful technique for the modification of sesame protein isolates.
Keywords: structural properties; rheological properties; Chemical technology; sesame protein; high-intensity ultrasound; technofunctional properties; structural properties; rheological properties; technofunctional properties; high-intensity ultrasound; TP1-1185; sesame protein; Article